Metal trafficking for nitrogen fixation: NifQ donates molybdenum to NifEN/NifH for the biosynthesis of the nitrogenase FeMo-cofactor - Hernandez, Jose A. (2008)
The molybdenum nitrogenase, present in a diverse group of bacteria and archea, is the major contributor to biological nitrogen fixation. The nitrogenase active site contains an iron-molybdenum cofactor (FeMo-co) composed of 7Fe, 9S, 1Mo, one unidentified light atom, and homocitrate. The nifQ gene was known to be involved in the incorporation of molybdenum into nitrogenase. Here we show direct biochemical evidence for the role of NifQ in FeMo-co biosynthesis. As-isolated NifQ was found to carry a molybdenum-iron-sulfur cluster that serves as a specific molybdenum donor for FeMo-co biosynthesis. Purified NifQ supported in vitro FeMo-co synthesis in the absence of an additional molybdenum source. The mobilization of molybdenum from NifQ required the simultaneous participation of NifH and NifEN in the in vitro FeMo-co synthesis assay, suggesting that NifQ would be the physiological molybdenum donor to a hypothetical NifEN/NifH complex.